PENDAMPINGAN PELAKSANAAN PEMBELAJARAN TERINTEGRASI BAHASA IBU KELOMPOK A DI TK NEGERI HARAPAN KOELODA - Ita, Efrida; Maria Fono, Yasinta; Florensa Dhema, Magdalena; Ota Beru, Valensia (Jurnal Pengabdian Kolaborasi dan Inovasi IPTEKS, 2023)
It has been identified that mother tongue is the language that children understand and use in their daily lives. Children communicate using this language before being introduced to other languages. The high intensity of the use of the mother tongue by children means that children do not easily follow and understand explanation or material given by teachers at school using a different language, namely Indonesian. The use of different language ​​for children creates problems in the learning process and is a concern for teachers to determine the appropriate language of instruction. One of the languages ​​of instruction is the mother tongue. The aim of this service activity is to provide assistance to teachers in implementing mother language-based learning. The methods of implementing service were observation and face-to-face discussions. This service activity was carried out at the Koeloda State Kindergarten as one of the target schools for using mother tongue in learning activities. The result of the mentoring activities is that the learning process becomes more dynamic where children are very enthusiastic in playing and learning activities so that they are able to create encouraging learning situation and provide learning motivation for children through the use of the language that the child has mastered.